2019
DOI: 10.1101/2019.12.16.878397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High fat diet worsens pathology and impairment in an Alzheimer’s mouse model, but not by synergistically decreasing cerebral blood flow

Abstract: Obesity is linked to increased risk for and severity of Alzheimer's disease (AD). Cerebral blood flow (CBF) reductions are an early feature of AD and are also linked to obesity. We showed that non-flowing capillaries, caused by adhered neutrophils, underlie the CBF reduction in mouse models of AD. Because obesity could exacerbate the vascular inflammation likely underlying this neutrophil adhesion, we tested links between obesity and AD by feeding APP/PS1 mice a high fat diet (Hfd) and evaluating behavioral, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 57 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Our results demonstrate that a Western-type diet applied to female pigs increases brain lipoxidative damage, an effect that can be reversed by applying a probiotic n3supplemented diet. Numerous studies have indicated a correlation between obesity and the risk of developing AD [1,4,32,33]. This risk represents a modifiable factor in neurodegenerative processes [1,4], suggesting that dietary components could serve as preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrate that a Western-type diet applied to female pigs increases brain lipoxidative damage, an effect that can be reversed by applying a probiotic n3supplemented diet. Numerous studies have indicated a correlation between obesity and the risk of developing AD [1,4,32,33]. This risk represents a modifiable factor in neurodegenerative processes [1,4], suggesting that dietary components could serve as preventive measures.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies, including our own, are in line with these clinical observations. Inducing metabolic disease via consumption of a high fat (HF) diet has been shown to worsen AD pathology and cognitive deficits in animal models (5,(15)(16)(17)(18)(19). Previously, we reported that consumption of a HF diet from ~3-7 months of age in 3xTg-AD mice resulted in a wider array of cognitive deficits (20) as well as more severe weight gain, glucose intolerance, and hypothalamic inflammation in females compared to males (5).…”
Section: Introductionmentioning
confidence: 99%